Extending the ARC (Ask, Record, Confirm) Technique to Enhance Real-Time Member Checking: A Case Study at Malaysia’s Transport License Department - Saadan, Naharudin bin; Khairi, Khairil Faizal bin; Mohd Zairul; Ahmad, Azuan bin; Tahir, Agoos Munalir bin (Universitas Muhammadiyah Makassar, 2025)
This study introduces the Extended ARC (Ask, Record, Confirm) technique as a methodological innovation for enhancing real-time member checking in qualitative focus group discussions (FGD). Building on the original ARC technique, the Extended ARC integrates physical and digital tools to improve transparency and rigour in data validation. Conducted at the Transport License Department (TLD) with operational officers engaged in a blockchain-based e-payment workflow, the method employed Google Forms for structured engagement, Google Sheets for real-time visualisation, and ATLAS.ti 25 for analysis. Implemented in seven phases that begin with preparation, logistics setup, thematic discussion, response submission, live monitoring, clarification, and final validation. The process enabled dynamic capture, refinement, and confirmation of participant input during the session. Real-time validation reduced the need for post-session transcription and strengthened the trustworthiness, dependability, and confirmability of findings. A deductive thematic analysis of the verified data yielded insights into blockchain’s suitability for improving inter-organisational collaboration workflow in the e-payment systems. By addressing the limitations of conventional member checking, the Extended ARC demonstrates methodological innovation, contextual adaptability, and offers a replicable framework for qualitative research in complex institutional environments.